Pecoah Kohon: The Restriction on Inter-Cousins Marriage in Indigenous the Rejang Society - Supardi Mursalin; Siti Nurjanah; Abraham Ethan Martupa Sahat Marune; Muhamad Hasan Sebyar; Hina Al Kindiya (Institut Agama Islam Negeri Batusangkar, 2023)
This study aims to examine the prohibition of Pecoah Kohon in the indigenous marriage Rejang tribe. Pecoah Kohon is a union between a man and woman related by blood, namely one grandmother. In this study, the problem emphasized a customary prohibition on the union, regardless of its non-prohibition by Islam. This qualitative-field analysis used a normative-sociological approach, with the implemented data collection techniques prioritizing interviews and documentation. A purposive sampling technique was also used to determine the informants. The results showed that the survival of Pecoah Kohon tradition was due to the socialization carried out by traditional officials in a systematic, structured, and hierarchical pattern toward the Rejang community. Sanctions were also considered quite strict against customary violations. Moreover, the good communication and cooperation between traditional officials and the community was a strong foundation for the preservation of Pecoah Kohon tradition and the Islamic religious insights of the Rejang community were increased. From this context, the debate about the tradition had various meeting points and solutions. This indicated that Pecoah Kohon supporters believed the tradition did not include prohibitions and cancellations of marriage, with its performance considered a tribute and cultural preservation. Religious experts also understood that Pecoah Kohonwas solely a custom and not a belief exceeding or equalling religion, indicating needless argumentative efforts.